KONSERVASI PALA (Myristica fragrans Houtt) SUATU ANALISIS TRI STIMULUS AMAR PRO-KONSERVASI KASUS DI KABUPATEN BOGOR - Tresika Deryanti; Ervizal AM ZUhud; Rinekso Soekmadi (Media Konservasi, 2014)
In Bogor, the ex situ conservation of nutmeg is a biodiversity conservation that supported by village ecosystem approximation based on community. The study about community motivation factors for doing conservative action would provide information about community willingness prerequisite those. The study was conducted in Dramaga, Caringin, and Cijeruk May until November 2012 with total 115 respondent. The result from correlation analysis 13 variables that related with nutmeg conservation are occupation that significantly influenced (confidence value 95%), income, cost of living, land size, distance between house and land, (knowledge about which seed is good, germinating seed method, planting method, nursing method, and harvesting method) that come into natural stimulus; (knowlwdge about what part of plant that used and understanding line of traffic nutmeg trade) that come into benefit stimulus; and that was planted by respondent (not inherited) come into willing stimulus significantly influenced (confidence value 99%). From all those stimulus, the main prerequisite motivating community willingness for doing conservation is small size plant therefore can be planted around yard of their house. Result from factor analysis, dependent variable (nutmeg conservation or total nutmeg which have is influenced by independent variable; income respondent (X3) and land size (X4) with equation Y= 2.300 X3 + 0,0006X4.  Keyword: Benefit stimulus, Ex situ conservation, Natural stimulus, Nutmeg, Willing stimulus